Preservative methods for autologous peripheral blood stem cells collected from Thai patients with multiple myeloma - Shaengkhamnang, Banphot; Panyajai, Pawaret; Chiampanichayakul, Sawitree; Tima, Singkome; Chaiwongsa, Rujirek; Thumvijit, Tarika; Klangsinsirikul, Phennapha; Tantiworawit, Adisak; Anuchapreeda, Songyot (Journal of Associated Medical Sciences, 2020)
Background: Bone marrow transplantation in multiple myeloma patients is one of the methods for multiple myeloma therapy. Blood stem cell preservation is very important for transplant therapy. Thus, preservative methods of peripheral blood stem cells (PBSCs) must be evaluated for successful transplantation. Objectives: The aim of this study was to collect and preserve autologous peripheral PBSCs (CD34+/CD38-) from multiple myeloma patients at 4°C and deep-freezing. Materials and methods: PBSCs were collected by leukapheresis before being cryopreserved and kept in liquid nitrogen. The number of CD34+/CD45dim cells were investigated and subpopulation CD34+/CD38- cells were evaluated by trypan blue exclusion method and 7-AAD by flow cytometry before and after cryopreservation. Results: The result showed that CD34+/CD38- cells constituted 45.08% of total CD34+ cells and 0.56% of total nucleated cells (TNCs). After thawing, CD34+/CD38- cell number did not show significant differences when compared to pre-storage. The CFU recovery after cryopreservation and storage at 4°C for 7 days were 93.53±5.83 and 63.77±12.40%, respectively. Storage at 4°C for 7 days showed significant decrease when compared to day 1. The remaining of total CFU after deep-freezing and storage at 4°C confirmed the tolerant and robust recovery of CD34+/CD38- cells. The engraftments of deep-freezing cells were 100% successful within 11 days without graft failure. Conclusion: In this present study, we assess the process of storage for high quality and recovery of PBSCs at 4°C within 3 days and cryopreservation for development of autologous hematopoietic stem cell (HSC) transplantation in multiple myeloma patients. Moreover, these conditions are important data guideline for HSC preservations and applications in the future.